Bronchoscopy during the COVID-19 pandemic: A Canadian Thoracic Society position statement. Issue 4 (4th July 2021) - Houston, Simon A.; McDonald, Christine M.; Tyan, Chung-Chun; Fortin, Marc; Sakr, Lama; Gillson, Ashley-Mae E.; Myers, Renelle; Bendiak, Glenda N.; Dumoulin, Elaine; Gonzalez, Anne V.; Hergott, Christopher A.
Abstract: This position statement aims to provide rapid guidance for those performing bronchoscopy in the pediatric and adult populations during the COVID-19 pandemic. These recommendations are based on the consensus of the authors, who are members of the Canadian Thoracic Society (CTS) Chest Procedures Assembly, and on the information available at the time this document was written, including guidance from other organizations. Changes in our understanding of COVID-19 and the course of the pandemic may affect the recommendations in this statement. Guidance from local public health authorities and from institutional infection prevention and control departments should be considered when assessing information in this document. Readers should consult these resources as they adapt plans for bronchoscopy during the pandemic. We plan to update this guidance regularly as new information becomes available, and recommend periodically checking the Canadian Thoracic Society website (https://cts-sct.ca/covid-19/) for updates.